1993
DOI: 10.1152/ajpheart.1993.264.4.h1239
|View full text |Cite
|
Sign up to set email alerts
|

Near-wall excess of platelets induced by lateral migration of erythrocytes in flowing blood

Abstract: In this study we present experimental data on the inhomogeneous distribution of platelets in polyethylene tubes (200 microns diam) based on the inverse Fåhraeus effect for platelets. It is shown that platelets are expelled toward the red blood cell-depleted marginal layer near the tube wall by mutual interaction with erythrocytes. By means of a straightforward model, the near-wall concentration of platelets could be estimated from measurements on the average tubular platelet concentration. The marginal layer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 14 publications
2
60
1
5
Order By: Relevance
“…In addition we have not modelled the effects of lift on the red blood cells away from the vessel wall. This creates a RBC-depleted marginal layer lying at the edge of a vessel (typical width 2-4 μm [17]) in which shear-induced diffusion is (presumably) reduced and which will also lead to an additional outwardly directed radial force on the targeted particles in opposition to the lift on RBCs away from the vessel wall (this force is observed on platelets and other small blood borne particles [26]). Furthermore, we have omitted from our discussion the effect of the vessel wall on the particle motion which becomes significant when the particle is a distance of the order of its radius from the vessel wall; these are treated in considerable detail for a spherical particle in [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition we have not modelled the effects of lift on the red blood cells away from the vessel wall. This creates a RBC-depleted marginal layer lying at the edge of a vessel (typical width 2-4 μm [17]) in which shear-induced diffusion is (presumably) reduced and which will also lead to an additional outwardly directed radial force on the targeted particles in opposition to the lift on RBCs away from the vessel wall (this force is observed on platelets and other small blood borne particles [26]). Furthermore, we have omitted from our discussion the effect of the vessel wall on the particle motion which becomes significant when the particle is a distance of the order of its radius from the vessel wall; these are treated in considerable detail for a spherical particle in [10].…”
Section: Discussionmentioning
confidence: 99%
“…This effect also indicates that the erythrocytes do not follow exactly the motion of the blood plasma, which implies that they may not always be suitable as ''natural'' tracer particles for blood flow measurements. Uijttewaal et al (1993Uijttewaal et al ( , 1994 showed that platelets experience a reversed Fåhraeus-Lindquist effect and concentrate in the erythrocyte-depleted layer. Plasma consists mainly of water.…”
Section: Fluid Mechanical Properties Of Bloodmentioning
confidence: 99%
“…28 Under normal circumstances, red cell flow is maximal at the center of a vessel, tending to push platelets towards the periphery of the vessel lumen, thereby optimizing their interaction with injured endothelium and promoting hemostasis. 29,30 At present the optimal hematocrit/hemoglobin concentration to avoid/treat a hemostatic disorder remains unknown. Limited experimental evidence suggests that hematocrits higher than those required to provide a normal oxygen delivery, and possibly as high as 35%, may be required to sustain hemostasis in bleeding patients.…”
Section: Should Recommendations For Rbc Transfusions Be Reconsidered?mentioning
confidence: 99%